Peranan Kantor Pertanahan dalam Perlindungan Lahan Pertanian Pangan Berkelanjutan di Kota Tebing Tinggi - Hulu, Fonaha; Mardayanti, Imelda (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This research is a descriptive study of the role of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency in providing protection for sustainable food agricultural land for the people in the city of Tebing Tinggi. Data preparation for Sustainable Food Agriculture Land (LP2B) is carried out through inventory, identification, and data processing activities for Sustainable Food Agriculture areas. This activity is in line with the duties and functions of the Land Arrangement Division of the Provincial BPN Regional Office as well as the District/City Land Office Arrangement section. This research method is qualitative with data collection carried out through document studies and interviews. The City of Tebing Tinggi does not yet have a Regional Regulation or Mayor's Regulation that regulates the planning, determination and protection of Sustainable Food Agricultural Land (LP2B) and Regional Regulations on Detailed Spatial Planning (RTDR), even though the determination of Sustainable Food Agricultural Land is part of the stipulation in the form of a plan. detailed spatial layout of the regency/city. Socialization (LP2B) in the City of Tebing Tinggi has not been optimal. More intensive collaboration and communication between agencies that are stakeholders related to the protection of Sustainable Food Agricultural Land (LP2B) is also not optimal.